XXV. mezinárodní kolokvium o regionálních vědách Sborník příspěvků - Rehák, Štefan (Masaryk University Press, 2022)
Title in English: 25th International Colloquium on Regional Sciences: Conference proceedings The conference proceedings consists of papers presented at the 25th International Colloquium on Regional Sciences that was organized by Department of Regional Economics and Administration FEA MU. It contains 57 articles arranged by topic. The individual articles deal with e.g. socioeconomic disparities among regions, regional policy, territory attractiveness, tourism, or regional public administration.